GRAMMATICAL COHESION IN STUDENTS' WRITING: A CASE AT UNIVERSITAS TEKNOKRAT INDONESIA - Afrianto Afrianto (UIN Raden Mas Said Surakarta, 2017)
This research aims at investigating the type of cohesive devices in students’ writing as a part of discourse analysis. Thus, it explores sentence correlation and meaning as a whole discourse and figures out inappropriate use of the devices.This research is conducted qualitatively to the students of English Letters of Universitas Teknokrat Indonesia Bandar Lampung and employs Halliday and Hasan’s (1976) conceptual framework. Further, examining the grammatical cohesion through document, this research deeply looks at the data in form of sentences. The researcher found 122 grammatical cohesive devices from three essays. Furthermore, the researcher also found 5 inappropriate uses of cohesive devices; it includes 2 additive conjunctions, 2 adversative conjunctions, and 1 temporal conjunction. It is also noted that the lacking understanding and awareness about cohesion especially on grammatical cohesion leads the students to use inappropriate cohesive devices. It then problematizes the semantic relation among ideas in the text. Thus, this research comes up with a feedback to the lecturer that the discussion of coherence and cohesion should be more intensive.